pTripleTREP – A vector for tightly controlled expression and purification of virulence factors in Staphylococcus aureus - Hannes Wolfgramm; Christopher Saade; Marco Harms; Larissa M. Busch; Josephine Lange; Maximilian Schedlowski; Kristin Surmann; Manuela Gesell Salazar; Christian Hentschker; Leif Steil; Stephan Michalik; Uwe Völker; et al. (Microbial Cell Factories)
Abstract Background Recombinant proteins facilitate and contribute to detailed studies of the virulence mechanisms and pathophysiology of the major human pathogen Staphylococcus aureus. Of particular interest are secreted virulence factors. However, due to their potential toxicity and specific post-translational processing, virulence factors are difficult targets for heterologous protein production. Purified proteins with native conformation and adequate purity can therefore often only be achieved by elaborate multi-step purification workflows. While homologous expression in S. aureus theoretically offers a promising alternative in this regard, its application remains limited due to the lack of systems that ensure both tightly controlled expression and subsequent efficient purification. Results To bridge this gap, we present pTripleTREP as a versatile expression vector for S. aureus, which enables the homologous expression and purification of staphylococcal virulence factors. It features a strong SigA-dependent staphylococcal promoter overlapped by three tetracycline responsive elements (TRE), which ensures tight repression under control conditions and high expression levels upon induction of the target gene. This allowed very precise controlled production of the exemplary targets, serine protease-like protein A (SplA) and B (SplB). A simple single-step protein purification workflow using a Twin-Strep-tag and Strep-Tactin®XT coated magnetic beads yielded endotoxin-free Spl samples with purities above 99%. Thereby, the homologous production host facilitates native secretion and maturation without the need to engineer the target gene sequence. Proper signal peptide cleavage and the corresponding enzymatic activity of the generated protein products were confirmed for SplA and B. Conclusion The expression vector pTripleTREP adds an important element to the staphylococcal molecular toolbox, facilitating the tightly controlled homologous expression and rapid native purification of secreted staphylococcal virulence factors. The optimised architecture and genetic features of the vector additionally provide a solid background for further applications such as plasmid-based complementation or interaction studies. Thus, pTripleTREP will support research on the role of staphylococcal virulence factors, paving the way for future therapeutic strategies to combat this pathogen.